Heritage Homestead Transformation into Rural-Urban Hybrid Environment: Conditions and Challenges - Raudonikyte, Indraja; Grazuleviciute-Vileniske, Indre (Landscape Architecture and Art, 2024)
Hybridization trends between urban and rural environments, where rural environments gain urban characteristics, some rural spatial and lifestyle characteristics remain present in peri-urban and suburbs areas which previously constituted a part of countryside as well as emerging high-tech and low-tech farming trends in the urban environment are commonly observed in developed and developing countries. Lithuania is not an exception from this trend of hybridization of environments. The recent shift of attention of urban dwellers to the countryside during the pandemics with the emergence of new hybrid environments and lifestyles there, justify the aim of this research - to analyse and understand better theoretical and practical premises of creation of hybrid environments in the countryside by transforming historical homesteads and developing sustainability aesthetics. This research includes: quantitative and qualitative literature review and theoretical analysis of hybrid environments and the peculiarities and state of research of such environments in the countryside (rural) context; the analysis of practical aspects of transformation of historical homesteads into hybrid environments in Lithuanian landscape focusing on interaction of tradition, practical aspects, and aesthetics.